Assessing the mediating effect of live video game streaming platform to the factors that influence viewer participation and the level of participation of the viewers - Foncardas, Jade Gabriele T. (Animo Repository, 2022)
Live video game stream has been around for a few years but only during the time of the pandemic did many utilize this as a way to both entertain themselves (viewer perspective) and earn from it (streamer perspective). The study focuses on assessing if streaming platforms has a mediating effect to both factors that influence viewer participation in live video game streaming and the viewer’s level of participation in the said stream. Here, the researchers found that Equipment, Motivation, Knowledge and Skills, Attitude and Personality, Gift-Giving, Games, Interactivity, Influencer and Affiliate Marketing, and Physiognomy have a significant positive effect to Viewer Participation individually. Collectively, changes in significance were seen wherein Knowledge and Skills, Gift-Giving, and Physiognomy were no longer significant. At the same time, Streaming Platforms was seen to significantly mediate the relationship between the factors aforementioned and Viewer Participation. Future study on the industry of live video game streaming is highly suggested by the researchers, specifically finding other factors that may affect Viewer Participation, combining current factors with other variables that future researchers may discover, or delving into specific elements of the stream, like the platforms used, games played, streamers’ actions, and the like. Results of the quantitative data analyses also matched with the qualitative data analyses (Pattern Matching), wherein data used was from the interviews conducted by the researchers with Live Video Game Streamers.